Computational collective intelligence : 11th international conference, ICCCI 2019, Hendaye, France, September 4-6, 2019 : proceedings.: 11th international conference, ICCCI 2019, Hendaye, France, September 4-6, 2019 : proceedings. Part I ([2019]) - Unknown
No abstract available